IMPROVING REGIONAL SERVICE CENTERS AND DEVELOPING SERVICE CULTURE (Web of Technology: Multidimensional Research Journal, 2025)
This scientific article analyzes the issues of improving the activities of regional service centers and developing service culture. The study examines the current state of regional service centers and identifies factors affecting service quality, professional and communicative competencies of employees, and customer relations culture. In addition, scientifically grounded proposals and recommendations aimed at enhancing the competitiveness of regional service centers through the development of service culture have been developed. The research results have practical significance for improving service quality and ensuring the socio-economic development of regions.